TO EXPLORE THE ROLE OF PHILOSOPHY FOR THE ATTAINMENT OF PEACE: AN HISTORICAL INTERPRETATION OF PEACE EDUCATION - Tariq Mehmood Bhuttah , Samina Sarwat , Faiz Farid , Amna Bibi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This article discusses the widely perceived state of perplexity over the philosophical basis of peace studies. Humans are born neither totally passive nor with the intrinsic morality of some sort. A man has an intrinsic tendency to favor goodness and mutual cooperation by showing decency of some sort. The study deals with the changes in the concept of peace, limited to Europe and the period between the 14th and 19th century. This study describes the aspiration of peace education that one should give priority and contribute to peace and reconciliation. The philosophies of peace education in ancient, modern and postmodern times of many educated men, social scientists, philosophers, and theorists such as Plato, Aristotle, Confucius, Augustine, Erasmus, Kant, Jean-Jacques Rousseau, John Dewey, Johan Galtung, Calleja, Harris and Morrison, Reardon and Page’s are discussed in this research.